Pembuatan Bio-Oil Dari Tandan Kosong Sawit Dan Pelepah Sawit Dengan Teknologi Pirolisis Menggunakan Katalis Ni/NZA - Anwar Sumianto; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Estimated consumption of petroleum will increase until 2015 reached 610 million barrel, while supply production of petroleum decrease untill 280 million barrel at 2025 years.. Therefore, there was estimated that oil stock will run out about 24 years away. Consesquently, it was necesarry alternative fuels to replace petroleum oil, one of them was by converting biomass into bio-oil with pyrolysis technology and catalyst. The purposes of this research was to determined physical and chemical characteristic of bio-oil that produced from oil palm empty fruit bunches and palm fronds, determined the effect of impregnation Ni metal to the resulting yield, and then determined the effect of the amount of catalyst to bio-oil yield. Pyrolisis processes carried out 50 gram oil palm empty fruit bunches or palm fronds (-100 + 200 mesh), Ni/NZA with ratio of metal (0%,1 %, 2% and 3% by weight percetage) and ratio of weight catalyst (3%, 5 % and 7 % by weight percetage) and 500 ml silinap at 3200C, stirred 300 rpm with nitrogen gas flow. The highest yield obtained on theratio weight of catalyst used 7% and 3% ratio of Ni metal were amounted at 67,9% for oil palm empty fruit bunches and 56,2% for palm fronds. Characteristic of the production of bio-oil were 1,014 gr/ml density, 9,096 cSt viscosity, the acid number was 43,10 mg NaOH/gr sample and flash point at 510C for empty fruit brunches, were 0,991 gr/ml density, 7,370 cSt viscosity, the acid number was 23,929 mg NaOH/gr sample and flash point at 540C for palm fronds. From the GC-MS analysist, the dominant compound from bio-oil were 2,4,4-trimethyl-2-pentene, 5,5-dimethyl 2-hexene, 3-(3.3-dimethylbutyl)-cyclohexanone and 1-ethyl-1-methyl cyclohexane. Keywords : bio-oil, catalyst Ni/NZA, palm frond, palm empty fruit bunches, and pyrolysis